Factors influencing awareness of healthcare providers on maternal sepsis: a mixed-methods approach - Vanessa Brizuela; Mercedes Bonet; João Paulo Souza; Özge Tunçalp; Kasisomayajula Viswanath; Ana Langer (BMC, 2019)
Abstract Background An awareness campaign set to accompany the Global Maternal Sepsis Study (GLOSS) was launched in 2017. In order to better develop and evaluate the campaign, we sought to understand the factors that influence awareness of maternal sepsis by exploring healthcare providers' knowledge, perception of enabling environments, and perception of severity of maternal sepsis. Methods We used a mixed-methods approach that included 13 semi-structured interviews to GLOSS regional and country coordinators and 1555 surveys of providers working in GLOSS participating facilities. Directed content analysis and grounded theory were used for qualitative analysis, based on a framework including four overarching themes around maternal health conditions, determinants of maternal health, barriers and facilitators to sepsis identification and management, plus 24 additional sub-topics that emerged during the interviews. Descriptive statistics for frequencies and percentages were used for the quantitative analysis; significance was tested using Pearson χ2. Logistic regressions were performed to adjust for selected variables. Results Analysis of interviews described limited availability of resources, poor quality of care, insufficient training and lack of protocols as some of the barriers to maternal sepsis identification and management. Analysis from the quantitative survey showed that while 92% of respondents had heard of maternal sepsis only 15% were able to correctly define it and 43% to correctly identify initial management. Provider confidence, perceived availability of resources and of a supportive environment were low (33%, 38%, and 48% respectively). Overall, the predictor that most explained awareness was training. Respondents from the survey and interviewees identified sepsis among the main conditions affecting women at their facilities. Conclusions Awareness on maternal sepsis, while acknowledged as important, remains low. Healthcare providers need resources and support to feel confident about the correct identification and management of sepsis, as a prerequisite for the improvement of awareness of maternal sepsis. Similarly, providers need to know about maternal sepsis and its severity to understand the importance of reducing sepsis-related mortality and morbidity. Awareness raising campaigns can help bring neglected maternal health conditions, such as sepsis, to the forefront of global and local agendas.